2021
DOI: 10.3389/fpls.2021.675546
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Regulation of CO2 Assimilation Enables Greater Resilience to High Temperature and Drought in Maize

Abstract: Increasing temperatures and extended drought episodes are among the major constraints affecting food production. Maize has a relatively high temperature optimum for photosynthesis compared to C3 crops, however, the response of this important C4 crop to the combination of heat and drought stress is poorly understood. Here, we hypothesized that resilience to high temperature combined with water deficit (WD) would require efficient regulation of the photosynthetic traits of maize, including the C4–CO2 concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 104 publications
(152 reference statements)
1
8
0
Order By: Relevance
“…The genotypes from the warm–dry climate ( Altiplano ) were the most affected, even for the two other crops. Studies showed that early closure of stomata and decreasing transpiration were found to be thermal sensitive in maize plants grown at high temperatures [ 63 ], as we reported in our study. In various crop species, such as soybean, tobacco, and grape, global warming has been found to increase stomatal frequency while decreasing stomatal size, though no effect has been recorded in maize [ 64 , 65 , 66 ].…”
Section: Discussionsupporting
confidence: 87%
“…The genotypes from the warm–dry climate ( Altiplano ) were the most affected, even for the two other crops. Studies showed that early closure of stomata and decreasing transpiration were found to be thermal sensitive in maize plants grown at high temperatures [ 63 ], as we reported in our study. In various crop species, such as soybean, tobacco, and grape, global warming has been found to increase stomatal frequency while decreasing stomatal size, though no effect has been recorded in maize [ 64 , 65 , 66 ].…”
Section: Discussionsupporting
confidence: 87%
“…In the NAD-ME type plants, the enzyme has the main function of decarboxylation of malate to produce pyruvate, NADH and CO 2 ; this enzyme uses NAD + , does not decarboxylate Oxalo Acetic Acid (OAA) and is present in mitochondria. Drought and C 4 enzymes, specifically the NAD and NADP malic enzyme action dynamics, have been well studied [ 14 , 67 , 69 , 70 ]. The possible mechanism can be that the entry of CO 2 is restricted under eCO 2 conditions due to reduction in stomatal density and closure, either due to eCO 2 or drought; the ME in C 4 can contribute to higher accumulation of CO 2 in the bundle sheath cells, thus increasing photosynthesis, and in contrast to the commonly accepted view that C 4 plants do not have a distinct advantage under eCO 2 conditions.…”
Section: Dry Matter Productionmentioning
confidence: 99%
“…In the NAD-ME type plants, the enzyme has the main function of decarboxylation of malate to produce pyruvate, NADH and CO2, this enzyme uses NAD + and does not decarboxylate Oxalo Acetic Acid (OAA) and is present in mitochondria. Drought and C4 enzymes specifically the NAD and NADP malic enzyme action dynamics have been well studied [67,69,70,14]. The possible mechanism can be that the entry of CO2 is restricted under eCO2 conditions due to reduction in stomatal density and also closure either due to eCO2 or drought, the ME in C4 can contribute to higher accumulation of CO2 in the bundle sheath cells, thus increasing photosynthesis, this is in contrast with the commonly accepted view that C4 plants don't have a distinct advantage under eCO2 conditions.…”
Section: Malate Maelstrommentioning
confidence: 99%